Insights into secondary reactions occurring during atmospheric ablation of micrometeoroids. (14th May 2016) - Court, Richard W.; Tan, Jonathan
Abstract: Ablation of micrometeoroids during atmospheric entry yields volatile gases such as water, carbon dioxide, and sulfur dioxide, capable of altering atmospheric chemistry and hence the climate and habitability of the planetary surface. While laboratory experiments have revealed the yields of these gases during laboratory simulations of ablation, the reactions responsible for the generation of these gases have remained unclear, with a typical assumption being that species simply undergo thermal decomposition without engaging in more complex chemistry. Here, pyrolysis–Fourier transform infrared spectroscopy reveals that mixtures of meteorite‐relevant materials undergo secondary reactions during simulated ablation, with organic matter capable of taking part in carbothermic reduction of iron oxides and sulfates, resulting in yields of volatile gases that differ from those predicted by simple thermal decomposition. Sulfates are most susceptible to carbothermic reduction, producing greater yields of sulfur dioxide and carbon dioxide at lower temperatures than would be expected from simple thermal decomposition, even when mixed with meteoritically relevant abundances of low‐reactivity Type IV kerogen. Iron oxides were less susceptible, with elevated yields of water, carbon dioxide, and carbon monoxide only occurring when mixed with high abundances of more reactive Type III kerogen. We use these insights to reinterpret previous ablation simulation experiments and to predict the reactions capable of occurring during ablation of carbonaceous micrometeoroids in atmospheres of different compositions.